Competitiveness Enablers in Handicraft Toy Manufacturing Industries Based on ISM-Fuzzy MICMAC Analysis - V. Meghasree; C. K. Nagendra Guptha (IEEE Access, 2025)
The traditional handicraft toy manufacturing industry, known for its unique craftsmanship and cultural significance, faces challenges that impact its competitiveness. These challenges restrict the industry’s ability to adapt to changing market demands. This study identified and analyzed the key enablers of competitiveness in the Channapatna handicraft toy manufacturing industry through a combined approach of Interpretive Structural Modeling (ISM) and Fuzzy Cross-Impact Matrix Multiplication Applied to Classification (MICMAC) analysis. Eleven critical competitiveness enablers were identified through qualitative data collection methods, including structured interviews with key stakeholders—artisans, retailers, government officials, and industry experts. ISM was used to structure the relationships, emphasizing their hierarchy and influence among these enablers. Fuzzy MICMAC analysis categorized these enablers according to their level of influence (driving power) and reliance (dependence power), providing insights into which enablers are essential for enhancing competitiveness. The results indicate that improving marketing techniques, enhancing branding, and fostering innovation are crucial drivers for industry growth. Furthermore, government support, financial assistance, and the adoption of technological advancements are significant enablers for sustaining long-term competitiveness. This study outlines strategies to guide policymakers, industry leaders, and stakeholders in revitalizing the Channapatna handicraft toy industry and effectively positioning it in domestic and global markets.